Acrylate azoamine chain extender as well as preparation method and application thereof

By using acrylate azoamine chain extenders, the mechanical properties and degradation ability of polyurethane are improved, the problem of limited degradation effect of polyurethane materials is solved, and the dependence on petroleum-based resources is reduced, and it is environmentally friendly.

CN119613288APending Publication Date: 2025-03-14WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311184781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing polyurethane materials have limited effect in degradation, and their production relies on petroleum-based resources, resulting in environmental pollution and resource depletion.

Method used

Acrylate azoamine chain extender is used, which contains amine groups and unsaturated double bonds in structure, which can react with isocyanate to form urea bonds, enhance the mechanical properties of polyurethane, and maintain fluidity and wetting by controlling the degree of reaction. At the same time, the chain extender can decompose under certain external conditions, promoting the decomposition of polyester polyols and enhancing the overall degradation ability of polyurethane.

Benefits of technology

It significantly improves the mechanical properties and degradation ability of polyurethane, solves the problem of limited degradation effect of polyurethane materials, and reduces dependence on petroleum-based resources, and has environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613288A_ABST
    Figure CN119613288A_ABST
Patent Text Reader

Abstract

The invention relates to an acrylate azo amine chain extender as well as a preparation method and application thereof. The acrylate azo amine chain extender has a general formula structure as shown in a formula (I): # imgabs0 #, and is obtained by reacting amino ethyl acrylate with an aromatic diamine monomer under the action of a metal catalyst. The amine chain extender provided by the invention can be used together with isocyanate and biodegradable polyester polyol to produce polyurethane related products. Due to the special structural design of the chain extender, the amine chain extender effectively improves the reaction operability and the physical performance of a product, meanwhile, in the degradation reaction process of the product, components for promoting the degradation reaction are continuously decomposed in a system, the degradability of the product is effectively improved, and the degradation speed of the product is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane, and specifically relates to an acrylate azoamine chain extender, a preparation method and application thereof. Background Art

[0002] Chain extenders are commonly used additives in polyurethane formulations. They can extend the hard segment molecular chain of the polymer, generate linear molecules with larger molecular weight, increase the hard segment content, and thus improve the overall mechanical properties of the product. Among them, amine chain extenders are an important type of chain extenders. Because they can react with isocyanates to form urea bonds, they have excellent mechanical properties. At the same time, they have high reactivity with isocyanates. Combined with the above characteristics, they can be used in polyurethane coatings, polyurethane elastomers, polyurethane adhesives and other fields.

[0003] Polyurethane is a cross-linked polymer material obtained by thermal curing reaction of isocyanate, polyester polyol or polyether polyol. The raw materials are completely dependent on petroleum-based resources. With the progress and development of society, petroleum resources are becoming increasingly depleted, which will inevitably limit the development of the polyurethane industry. At the same time, polyurethane materials are difficult to recycle after being discarded, and are also difficult to degrade in the natural environment, which is very likely to cause "white pollution". The methods for treating polyurethane waste are mainly landfill and incineration. "Landfill treatment" occupies land resources and causes soil degradation, while "incineration treatment" produces a large amount of toxic gases, which is easy to cause air pollution. Therefore, the development of environmentally friendly biodegradable polyurethane materials has become the focus of the materials field.

[0004] In recent years, the research on degradable polyurethane has become a hot topic of research. Patent CN112979912B provides a super-tough polylactic acid-based polyurethane urea material, which uses polylactic acid diol as a soft segment and obtains a degradable polyurethane material with excellent mechanical strength through formula adjustment. However, the degradable part in this system is only the polyol component, that is, the soft segment part in the polyurethane. A large number of hard segments that cannot be degraded are also retained, so that the degradation effect of the entire system is limited. Patent CN104387553A provides a method for preparing a biodegradable unsaturated polyurethane material, that is, using unsaturated polyester polyol polyfumaric acid propylene glycol ester as a soft segment, and utilizing the degradability of its polyester to achieve the biodegradation function of the material. At the same time, the main chain structure of the polyurethane has a large number of unsaturated electron-deficient double bonds, which can facilitate further modification of the material. Although the patent introduces an unsaturated double bond structure into the main chain structure, it does not play a favorable role in the degradability of the polyurethane. Summary of the invention

[0005] The object of the present invention is to provide an acrylic ester azoamine chain extender. The chain extender, due to the terminal amine contained in its own structure, reacts with isocyanate to form a urea bond, which can effectively improve the tensile strength, hardness and other mechanical properties of polyurethane products; the unsaturated double bond at the other end can control the degree of reaction, so that the macromolecular chain in the system will not be completely cross-linked, so that the system can maintain good fluidity and wettability for a long time, and the operability is greatly improved. At the same time, the polyurethane product using the chain extender can be guaranteed to decompose under certain external conditions. Because the chain extender belongs to the hard segment of the polyurethane, the degradation problem of the hard segment of the polyurethane can be solved by its own degradation; the ethanolamine monomer decomposed during the degradation process can effectively promote the decomposition of the polyester polyol in the system due to its own alkalinity, so that effective degradation can be achieved in both the soft and hard segments, and the overall degradation ability of the polyurethane product can be improved.

[0006] Another object of the present invention is to provide a method for preparing the acrylate azoamine chain extender.

[0007] Another object of the present invention is to provide an application of the acrylic ester azoamine chain extender.

[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0009] An acrylate azoamine having the general structure of formula (I):

[0010]

[0011] Among them, R1 is an alkyl group of C1-C5, for example, an alkyl group with 1, 2, 3, 4, or 5 carbon atoms, and the alkyl group may be a straight-chain alkyl group or a branched alkyl group, preferably an alkyl group of C1-C4; specifically, for example, CH2, CH2CH2, CH2CH2CH2, CH2CH2CH2CH2, CH2CH2CH2CH2CH2, etc., preferably any one of CH2, CH2CH2, and CH2CH2CH2; R2 is a group containing an aromatic ring or an alicyclic ring, that is, a group structure with at least one benzene ring or alicyclic ring, for example, diphenylmethane, dicyclohexylmethane, benzene, alkylbenzenes, etc.

[0012] In a specific embodiment, the structure of the acrylic ester azoamine chain extender is as follows:

[0013]

[0014] On the other hand, a method for preparing the aforementioned acrylate azoamine chain extender comprises the step of reacting alkyl acrylate with aromatic diamine or alicyclic diamine monomer in the presence of a metal catalyst to generate acrylate azoamine.

[0015] Wherein, the alkyl acrylate has the general structure of formula (II):

[0016]

[0017] In formula (II), the selection of R1 is consistent with that in the aforementioned formula (I).

[0018] The structural formula of the aromatic diamine monomer or alicyclic diamine monomer is NH2-R2-NH2, R2 is a group containing an aromatic ring or an alicyclic ring, and the selection of R2 is consistent with that in the aforementioned formula (I).

[0019] The reaction equation is:

[0020]

[0021] The molar ratio of alkyl acrylate to aromatic diamine or alicyclic diamine monomer is 1:1-5, for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:4.5, 1:5, etc., preferably 1:1-3.

[0022] The metal catalyst is selected from any one of zinc, bismuth and tin, and is usually a single metal, preferably zinc, such as zinc powder.

[0023] Among them, the added amount of the metal catalyst is 1-5% of the sum of the molar amounts of alkyl acrylate, aromatic diamine and alicyclic diamine monomers, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., preferably 2-3%.

[0024] The reaction temperature of the above-mentioned alkyl acrylate with aromatic diamine and alicyclic monomer is 60-120°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the reaction time is 2-5h, for example, 2h, 2.5h, 3h, 4h, 5h, etc.

[0025] In a specific embodiment, the preparation method of the acrylic ester azoamine chain extender includes: adding acrylic ester alkyl ester, aromatic diamine / alicyclic diamine and zinc powder catalyst into a reactor, reacting at 60-120° C. for 2-5 hours to generate acrylic ester azoamine.

[0026] In another aspect, the aforementioned acrylate azoamine chain extender or the acrylate azoamine chain extender prepared by the aforementioned preparation method is used in the preparation of polyurethane.

[0027] The acrylic ester azoamine chain extender of the present invention can be used alone or in combination with other chain extenders, for example, after being mixed with polyether and plasticizer, it can be used as a curing agent component for producing polyurethane related products, and the related products can be applied to composite materials, elastomers and other fields.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The acrylic ester azoamine chain extender of the present invention has an amine group at one end and an unsaturated double bond at the other end. Due to the special structure, the reaction process is divided into two parts. First, after mixing with isocyanate, the amine group at one end reacts quickly with isocyanate to generate a urea bond, completing the initial chain extension reaction; but at the same time, the unsaturated double bond at the other end plays a capping role, suspending the rapid progress of the chain extension reaction, avoiding the problem that the viscosity of the system increases too fast due to the high activity of the diamine chain extender, affecting the overall operability. This significantly reduces the activity of the reaction system in the first stage of the chain extension reaction, reduces the rate of increase of the viscosity of the system, significantly improves the fluidity and wettability, and is beneficial to the overall mechanical properties of the product. At the same time, since the isocyanate bond has reacted quickly with the amine in the first stage, the system has better operability while reducing the sensitivity to environmental humidity and improving the tolerance of the use environment. In the second stage of chain extension, the double bond at the end of the molecular chain is opened by external heating, so that the macromolecular chains in the system are completely cross-linked, achieving a complete maturation effect, and obtaining the final product. It can be seen that by using this type of new chain extender, the reaction process is more controllable. While ensuring the operability in the early stage, it can be fully matured as needed to obtain the final product.

[0030] The azoamine and ester bond structure in the acrylic ester azoamine chain extender of the present invention can be decomposed under certain external conditions (for example, under alkaline conditions, the azo bond breaks at an ambient temperature of 50°C to 70°C to generate two primary amine structures, and the ester bond is hydrolyzed under alkaline conditions to generate carboxylate and alcohol), that is, while the hard segment is decomposed in the manner of the chain extender, the system is alkaline due to the presence of the alcoholamine monomer, and the decomposition of polyester chain segments such as polylactic acid and polycaprolactone can be effectively promoted under alkaline conditions. While achieving the decomposition of the hard segment, it plays an effective role in promoting the degradation of the soft segment containing the polyester chain segment, thereby enhancing the overall degradation capacity of the polyurethane product. DETAILED DESCRIPTION

[0031] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0032] Some raw material sources:

[0033] MDA-100, IPDA, and HMDA were from Wanhua Chemical Group Co., Ltd.;

[0034] Aminoethyl acrylate, aminobutyl acrylate, and aminohexyl acrylate were purchased from Nanjing Qishi Biological Co., Ltd.;

[0035] MDI prepolymer: 200g C2020 polyether and 400g F3135 polyether were dehydrated at 110℃ for 2 hours, then cooled to 85℃ and added with 200g MDI50 for polymerization reaction to generate MDI prepolymer. Both polyether and MDI50 were from Wanhua Chemical Group Co., Ltd.

[0036] Example 1

[0037] (1) 2 mol of aminoethyl acrylate and 4 mol of HMDA are added to a dry reactor, and 0.24 mol of zinc powder catalyst is added. The reaction is carried out at 90° C. for 2.5 hours. After distillation, acrylic acid azoamine is obtained.

[0038] (2) 3 g of the chain extender prepared in step (1) was mixed with 30 g of C2020 polyether and 35 g of long-chain chlorinated paraffin, and after dehydration at 105° C. for 2.5 hours, the mixture was mixed with the MDI prepolymer in a mass ratio of 2:1 and mixed evenly using a stirrer.

[0039] According to the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely in the mold. Post-aging was carried out at 150 degrees for 8 hours. After curing at room temperature for 7 days, mechanical properties tests were carried out. Through a universal tensile machine, the tensile shear strength of the specimen was tested within the tensile speed range required by the national standard. The elongation at break could reach 3.4Mpa and 620%.

[0040] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml phosphate buffer solution (pH=7.2), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 12.5%.

[0041] Example 2

[0042] (1) 2 mol of aminobutyl acrylate and 2 mol of MDA100 are added to a dry reactor, and 0.04 mol of zinc powder catalyst is added. The reaction is carried out at 120° C. for 2 hours. After distillation, acrylic acid azoamine is obtained.

[0043] (2) 2 g of the chain extender prepared in step (1) was mixed with 20 g of C2020 polyether and 23 g of long-chain chlorinated paraffin, and after dehydration at 100° C. for 2 hours, it was mixed with MDI prepolymer in a mass ratio of 2:1 and mixed evenly using a stirrer.

[0044] According to the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely in the mold. Post-aging was carried out at 150 degrees for 8 hours. After curing at room temperature for 7 days, mechanical properties tests were carried out. Through a universal tensile machine, the tensile shear strength of the specimen was tested within the tensile speed range required by the national standard. The elongation at break could reach 3.8Mpa and 600%.

[0045] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml phosphate buffer solution (pH=7.2), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 13.6%.

[0046] Example 3

[0047] (1) 2 mol of aminoethyl acrylate and 6 mol of IPDA are added to a dry reactor, and 0.4 mol of bismuth catalyst is added. The mixture is reacted at 120° C. for 5 hours, and then distilled to obtain acrylic acid azoamine.

[0048] (2) 4 g of the chain extender prepared in step (1) was mixed with 25 g of F3135 polyether and 28 g of long-chain chlorinated paraffin, and after dehydration at 100° C. for 2 hours, it was mixed with MDI prepolymer at a mass ratio of 2.5:1 and mixed evenly using a stirrer.

[0049] According to the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely in the mold. Post-aging was carried out at 150 degrees for 8 hours. After curing at room temperature for 7 days, mechanical properties tests were carried out. Through a universal tensile machine, the tensile shear strength of the specimen was tested within the tensile speed range required by the national standard. The elongation at break could reach 3.2Mpa and 564%.

[0050] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml phosphate buffer solution (pH=7.2), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 12.9%.

[0051] Example 4

[0052] (1) 2 mol of aminohexyl acrylate and 10 mol of IPDA were added to a dry reactor, and 0.24 mol of a tin catalyst was added. The reaction was carried out at 60° C. for 5 hours. After distillation, acrylic acid azoamine was obtained.

[0053] (2) 8 g of the chain extender prepared in step (1) was mixed with 40 g of F3135 polyether and 58 g of long-chain chlorinated paraffin, and after dehydration at 100° C. for 2 hours, it was mixed with MDI prepolymer in a mass ratio of 3:1 and mixed evenly using a stirrer.

[0054] According to the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely in the mold. Post-aging was carried out at 150 degrees for 8 hours. After curing at room temperature for 7 days, mechanical properties tests were carried out. Through a universal tensile testing machine, the tensile shear strength of the specimen was tested within the tensile speed range required by the national standard. The elongation at break can reach 3.6Mpa and 552%.

[0055] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml phosphate buffer solution (pH=7.2), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 11.2%.

[0056] Example 5

[0057] (1) 3 mol of aminopropyl acrylate and 12 mol of HMDA are added to a dry reactor, and 0.45 mol of bismuth catalyst is added. The mixture is reacted at 100° C. for 2.3 hours. After distillation, acrylic acid azoamine is obtained.

[0058] (2) 3 g of the chain extender prepared in step (1) was mixed with 35 g of F3135 polyether and 48 g of long-chain chlorinated paraffin, and after dehydration at 100° C. for 2 hours, it was mixed with MDI prepolymer at a mass ratio of 2.5:1 and mixed evenly using a stirrer.

[0059] According to the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 2 hours, the mixture could still flow freely in the mold. Post-aging was carried out at 150 degrees for 8 hours. After curing at room temperature for 7 days, mechanical properties tests were carried out. Through a universal tensile machine, the tensile shear strength of the specimen was tested within the tensile speed range required by the national standard. The elongation at break could reach 3.3Mpa and 570%.

[0060] Degradation test: Cut a small sample of 10mm×10mm×5mm from the sample plate, immerse it in 25ml phosphate buffer solution (pH=7.2), place it in an environment of 37±1℃, take it out every 6-7 days, dry it in vacuum at 80℃ until it reaches constant weight, and then weigh it to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate reaches 12.0%.

[0061] Comparative Example

[0062] 2g 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA) was mixed with 20g C2020 polyether and 23g long-chain chlorinated paraffin, and after removing water at 100℃ for 2 hours, it was mixed with MDI prepolymer at a mass ratio of 2:1 and mixed evenly with a stirrer. According to the requirements of the national standard GBT19250-2013, 2.5mm thick standard mechanical properties test specimens were cast at room temperature. After 40 minutes, the mixture could not flow freely in the mold. Post-matured under heating conditions of 150 degrees, and matured and heated for 8 hours. After curing at room temperature for 7 days, the mechanical properties were tested. The tensile shear strength of the specimen can reach 3.0Mpa and the elongation at break can reach 520% ​​by using a universal tensile testing machine within the tensile speed range required by the national standard.

[0063] For the degradation test, a small sample of 10mm×10mm×5mm was cut from the sample plate, immersed in 25ml phosphate buffer solution (pH=7.2), placed in an environment of 37±1℃, taken out every 6-7 days, vacuum dried at 80℃ until constant weight, and weighed to calculate the percentage of mass reduction. After immersion for 20 days, the weight loss rate was 1.5%.

Claims

1. An acrylic ester azoamine chain extender, characterized in that: It has the general structure of formula (I): Among them, R1 is a C1-C5 alkyl group, and R2 is a group containing an aromatic ring or an alicyclic ring; preferably, R1 is selected from a C1-C4 alkyl group, more preferably any one of CH2, CH2CH2, and CH2CH2CH2; R2 is selected from any one of a group containing two benzene rings or two alicyclic rings, more preferably any one of diphenylmethane and dicyclohexylmethane.

2. A method for preparing the acrylic ester azoamine chain extender according to claim 1, characterized in that: The method comprises the steps of reacting alkyl acrylate with aromatic diamine or alicyclic diamine monomer in the presence of a metal catalyst to generate acrylate azoamine.

3. The method according to claim 2, characterized in that The alkyl acrylate has the general structure of formula (II): Wherein, R1 is a C1-C5 alkyl group; preferably, R1 is selected from a C1-C4 alkyl group, more preferably any one of CH2, CH2CH2, and CH2CH2CH2.

4. The method according to claim 2 or 3, characterized in that: The structural formula of the aromatic diamine monomer or alicyclic diamine monomer is NH2-R2-NH2, wherein R2 is a group containing an aromatic ring or an alicyclic ring; preferably, R2 is any one of a group containing two benzene rings and two alicyclic rings, preferably any one of diphenylmethane and dicyclohexylmethane.

5. The method according to any one of claims 2 to 4, characterized in that: The molar ratio of the aminoalkyl acrylate to the aromatic diamine or alicyclic diamine monomer is 1:1-5, preferably 1:1-3.

6. The method according to claim 2, characterized in that The metal catalyst is selected from any one of zinc, bismuth and tin, preferably zinc.

7. The method according to claim 6, characterized in that The amount of the metal catalyst added is 1-5%, preferably 2-3%, of the sum of the molar amounts of the alkyl acrylate, aromatic diamine and alicyclic diamine monomers.

8. The method according to any one of claims 1 to 7, characterized in that: The reaction temperature is 60-120°C and the reaction time is 2-5h.

9. Use of the acrylate azoamine chain extender according to claim 1 or the acrylate azoamine chain extender prepared by the preparation method according to any one of claims 2 to 8 in the preparation of polyurethane.

10. The use according to claim 9, characterized in that: The acrylic ester azoamine chain extender is used together with isocyanate and biodegradable polyester polyol.

Citation Information

Patent Citations

  • Biodegradable unsaturated polyurethane material and preparation method thereof

    CN104387553A

  • Super-tough polylactic acid-based polyurethane urea and its preparation method

    CN112979912B

  • Azobenzene-contained microcapsule-type liquid crystal and application thereof in light-controlled liquid-crystal falsification-resistant ink

    CN104861783A

  • Halogen modified azo diamine chain extender as well as preparation method and application thereof

    CN115322123A

  • Acrylonitrile modified azo diamine chain extender and preparation method thereof

    CN116178205A